2014
DOI: 10.1007/s12663-014-0644-6
|View full text |Cite
|
Sign up to set email alerts
|

Comparison Between Two Techniques for the Treatment of Mandibular Subcondylar Fractures: Closed Treatment Technique and Transoral Endoscopic-Assisted Open Reduction

Abstract: Purpose The endoscopic-assisted technique for the treatment of subcondylar fractures has been used successfully and its acceptance develops as more surgeons gain experience. We present the short term results of this technique in a randomized prospective clinical trial. Methods and Materials A total of 40 patients with mandibular subcondylar fracture were included in our study in two groups randomly. Patients of first group were treated by closed treatment technique and patients of second group by transoral end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 18 publications
1
11
0
Order By: Relevance
“…In this study, no significant difference was noted in maximum mouth opening between surgically and conservatively treated fractures. Similar results were noted by Santler et al ,[ 14 ] Khiabani et al ,[ 15 ] Haug and Assael. [ 16 ] Although immediate postoperatively maximum mouth opening was significantly higher (26.6 mm ± 1.50 mm) in conservatively treated patients than surgically treated patients (22.66 mm ± 1.54 mm), the patients treated by open methods may have had less mouth opening at 6 weeks because surgery induced some hypomobility due to joint and incisional pain, or possibly because scarring occurred during healing of the surgical site.…”
Section: Discussionsupporting
confidence: 91%
“…In this study, no significant difference was noted in maximum mouth opening between surgically and conservatively treated fractures. Similar results were noted by Santler et al ,[ 14 ] Khiabani et al ,[ 15 ] Haug and Assael. [ 16 ] Although immediate postoperatively maximum mouth opening was significantly higher (26.6 mm ± 1.50 mm) in conservatively treated patients than surgically treated patients (22.66 mm ± 1.54 mm), the patients treated by open methods may have had less mouth opening at 6 weeks because surgery induced some hypomobility due to joint and incisional pain, or possibly because scarring occurred during healing of the surgical site.…”
Section: Discussionsupporting
confidence: 91%
“…The treatment method is determined by the height of the ramus mandibulae and the angle of deviation of the bone fragment [14,15]. Although the fracture heals fast, some complications interfere with daily life, such as facial scarring, facial nerve paralysis, and ankylosis [16]. Reports suggest using endoscopy equipment and techniques to avoid these issues [17].…”
Section: Discussionmentioning
confidence: 99%
“…Aboelatta et al33 found a significant improvement in MIO postoperatively. Average MIO is reported in Khiabani et al40 found a greater maximal anterior opening in an endoscopic group compared to an MMF group at 2-and 4-week follow-up.…”
mentioning
confidence: 86%
“…Five studies reported MO as a primary outcome 33,35,36,40,42 . Aboelatta et al 33 found a significant improvement in MIO postoperatively.…”
Section: Endoscopic Approachesmentioning
confidence: 99%
See 1 more Smart Citation